Pengembangan Media Virtual Reality Berbasis Aplikasi Artsteps untuk Meningkatkan Hasil Belajar Seni Tari - Maulana, Muh. Fajar; Nurharini, Atip (FONDATIA, 2024)
Limitations in providing innovative learning media and in accordance with advances in science and technology provide limitations for students in understanding the material, lack of desire to learn, and low learning outcomes. The purpose of the research is to develop Virtual Reality learning media based on the Artsteps application that can be used to teach students the material of the supporting elements of dance in grade V Elementary School. The type of research used is Research and Development (R&D) using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). This study collected data through test and non-test techniques, the instruments used included questionnaires, interview sheets, expert validation sheets, and pre-test and post-test questions. Data analysis was done through normality test, T-test and N-gain. The results developed in the media in the form of music contained in each dance painting. Material expert validation shows an average score of 97% with "very feasible" criteria, while media experts get a percentage value of 93% with "very feasible" criteria. The effectiveness of using Virtual Reality learning media based on the Artsteps application shows 0.001 for the small-scale T-test and 0.000 for the large-scale T-test, both of which are included in the "High" criteria, indicating a change in behavior and for the N-gain test the average value for the small-scale test is 0.8918 and the average value for the large-scale trial is 0.8612, both of which are included in the "High" criteria. These results indicate that the Virtual Reality learning media based on the Artsteps application is very feasible to use.